Efficiency, concentration and competition in the brazilian banking sector: a comparative literature analysis - Wolters, Mark (2010)
The past two decades have seen a revolution in the Latin American banking industry with a rash of crises, reforms, deregulation, privatizations, and foreign bank investment. The region has become a hot bed of interest in global financial markets. Brazil in particular has seen a significant change in its banking sectors competitive makeup with increases in foreign bank participation and lessening of public bank burden on the federal government. Competition, consolidation, and efficiency measures throughout the region have led to a reexamining of the costs and benefits of consolidated banking sectors and the threat of monopolistic actions of banks. Possible statistical analytical tools for efficiency, concentration, and competition are discussed, such as the Panzer Rosse H-Statistic, Frontier Analysis, and others. The quiet life theory of a monopoly is examined and put up against the efficient structure hypothesis of Demsetz in order to see which theory may hold more credence in the Brazilian banking sector upon further research. The paper finished with the analysis of the Brazilian banking sector and how developments can we do in future research to expand and fortify the previous findings about Brazilian banking sector.